The Role of Fiber in Energy Balance - Kolderup, Astrid; Svihus, Birger (Journal of nutrition and metabolism, 2019)
Excessive energy intake is linked with obesity and subsequent diet-related health problems, and it is therefore a major nutritional challenge. Compared with the digestible carbohydrates starch and sugars, fiber has a low energy density and may have an attenuating effect on appetite. This narrative review attempts to clarify the net energy contributions of various fibers, and the effect of fiber on satiety and thus appetite regulation. Fibers, broadly defined as nonstarch polysaccharides, are a varied class of substances with vastly different physicochemical properties depending on their chemical arrangement. Thus, net energy content can vary from more than 10 kJ/g for soluble, nonviscous, and easily fermentable fibers such as those in many fruits, to less than zero for viscous fibers with anti-nutritive properties, such as certain types of fibers found in rye and other cereals. Likewise, some fibers will increase satiety by being viscous or contribute to large and/or swollen particles, which may facilitate mastication and increase retention time in the stomach, or potentially through fermentation and an ensuing satiety-inducing endocrine feedback from the colon. Thus, fibers may clearly contribute to energy balance. The metabolizable energy content is very often considerably lower than the commonly used level of 8 kJ per g fiber, and some fibers may reduce energy intake indirectly through satiety-inducing effects. A more precise characterization of fiber and its physicochemical effects are required before these beneficial effects can be fully exploited in human nutrition.